Common maternal health problems and their correlates in early post-partum mothers - Christine Ng; Anna Szücs; Lay Hoon Goh (Women's Health, 2024)
Background: Mothers experience a wide range of maternal health problems after childbirth, which in turn, affect their well-being and ability to care for their newborn. These problems may be influenced by factors such as mode of delivery or socio-economic status. Objective: This study aims to investigate the prevalence of common maternal health problems and their correlates in a public primary healthcare institution in Singapore. Design: This was a cross-sectional study, based on a self-administered questionnaire. Methods: A total of 373 mothers (mean age 31.9 years) who accompanied their infants for their 4- to 8-week development assessments at a public primary care clinic in Singapore completed a self-administered questionnaire from June 2021 to December 2021. The questionnaire assessed demographic factors, mode of delivery, number of children, number of individuals providing significant help, and the frequency of common physical and mental maternal health problems using a 5-point Likert-type scale. Results: The five most common maternal health problems were fatigue (77.7%), lower back pain (59.3%), Caesarean wound pain (54.3%), upper back pain (53.0%) and vaginal pain (41.2%). The prevalence of depression and anxiety was 22.0% and 11.3%, respectively. With respect to the symptoms’ correlates, pain on passing urine was more frequent after assisted vaginal deliveries than all other forms of deliveries (all pairwise p  < 0.01), and pain on passing motion was more frequent in vaginal deliveries than in Caesarean deliveries (all pairwise p  < 0.05). Mothers having a larger number of children more frequently experienced headaches (β = 0.17, SE = 0.05, p  = 0.002) and less frequently experienced breastfeeding difficulties (β = –0.28, SE = 0.08, p  < 0.001). Conclusion: Mothers experienced a high prevalence of maternal health problems in multiple domains during the first 8 weeks after childbirth. Mode of delivery and number of children were associated with increased prevalence of certain problems. Mothers’ physical and mental well-being should be investigated early after delivery and addressed with adequate treatments and resources.